Spremenjeno kristaljenje vodnega kamna pri magnetni obdelavi vode - Pristovnik, Andrej (Strojniški vestnik, 2000)
Magnetic water treatment (MWT) is an alternative method of supplied-water conditioning for scale control and is also important in the amelioration of other water-based fluids. The effects of MWT devices, such as the modified crystalization of the scale-forming components and modified stability of the dispersion are discussed with the emphasis on the modified hydration of ions and solid surfaces due to magnetic proton resonance as one of the possible mechanisms. In addition, a possible explanation for the accelerated aragonite precipitation is proposed.
Keywords: priprava vode; kristaljenje CaCo3; hidratacija ionska; magnetohidrodinamika; kristalizacija; vodni kamen